Cepharanthine Ameliorates Chondrocytic Inflammation and Osteoarthritis via Regulating the MAPK/NF-κB-Autophagy Pathway - Yao, Minjun; Zhang, Caihua; Ni, Lingzhi; Ji, Xiaoxiao; Hong, Jianqiao; Chen, Yazhou; Wang, Jie; Li, Congsun; Lin, Jiyan; Lu, Tingting; Sheng, Yihao; Sun, Menghao; et al. (Frontiers in Pharmacology, 2022)
Osteoarthritis is a worldwide joint disease caused by abnormal chondrocytic metabolism. However, traditional therapeutic methods aimed at anti-inflammation for early-stage disease are palliative. In the present study, we demonstrated that cepharanthine (CEP), extracted from plant Stephania cepharantha, exerted protective medicinal efficacy on osteoarthritis for the first time. In our in vitro study, CEP suppressed the elevated expression of matrix metalloproteinases (MMPs), a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5), cyclooxygenase 2 (COX2), and inducible nitric oxide synthase (iNOS) stimulated by IL-1β or TNF-α through inhibiting the activation of MAPK and NF-κB signaling pathways, and upregulated the protein expression of Aggrecan, Collagen II and Sox9. And meanwhile, CEP could reverse the reduced level of cellular autophagy in IL-1β or TNF-α-induced chondrocytes, indicating that the protective effect of CEP on osteoarthritis was achieved partly by restoring MAPK/NF-κB-mediated autophagy. Further, in a murine OA model, CEP mitigated cartilage degradation and prevented osteoarthritis in the CEP-treated groups versus the OA group. Hence, our results revealed the therapeutic prospect of CEP for anti-osteoarthritic treatment.